Influencing factors to the capillary water uptake of (un)cracked cementitious materials - De Brabandere Laurena; Van Mullem Tim; Alderete Natalia; Baeyens Dries; De Belie Nele (MATEC Web of Conferences, 2023)
Capillary water absorption tests are widely used in uncracked cementitious materials to assess the quality and durability. Due to the easy execution of the test, it is also frequently used to assess the self-healing efficiency of self-healing concrete and mortar. It is established that the presence of a crack significantly increases the water uptake by a specimen. However, it is not known how the crack width, healing agents and mix composition influence the capillary water absorption. In this research, for cylindrical mortar specimens with four different crack widths, both a capillary water absorption test and water permeability were test were executed in order to investigate the relation between these two test methods. After the first round of testing, cracked specimens were healed manually with polyurethane and methyl methacrylate and the capillary absorption test was performed again to investigate the sensitivity of the test method to different degrees of crack healing. Furthermore, prismatic specimens were cast to investigate the influence of crack creation and geometry. It was found that the crack width does not have an influence on the capillary absorption rate. However, the crack width has a significant influence on the water flow through the crack. As expected, manual healing with polyurethane is better in comparison to the sealing of the crack mouth with methyl methacrylate.